Prof. Bronius Balčytis, the author of course-books of mathematics - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2016)
Bronius Balčytis (born: Feb. 14, 1926) – Professor, Habilitated Doctor of Social Sciences. Member Lithuanian Mathematicians Society, Lithuanian SSR State Award laureate, 1982. Prepared: mathematics education system for Lithuanian three-year primary school, 1970–1973; methods system of compulsory mathematics education for 1st grade children, 1981–1989; mathematics program and methods system of education in Lithuanian primary school, 1991–1997. Author, 13 math. textbooks,12 books for teachers, 3 books for students and over 150 other publs. Over 30 of his books translated into Polish and over 20 – into Russian.
Keywords: didactics of mathematics; habilitated doctor; primary school; professor; textbooks